Purification and Characterization of Ulvans from Chilean Ulva Lactuca and Assessment of the Stimulation of Growth Induced by Ulvans and Oligo-Ulvans in Arabidopsis Thaliana - Moenne-Munoz, A; Gonzalez-Figueroa, A; Espinoza-Majmud, D (Springer, 2024)
To study the effect of ulvans and oligo-ulvans on the stimulation of growth in Arabidopsis thaliana, extracts of Chilean U. lactuca were prepared in water at pH = 7 and pH = 4, and ulvans were purified. The yield of ulvans was 16% of dry weight in both extracts and molecular weights were 115 kDa in extract at pH = 7 and 70 kDa in extract at pH = 4. Purified ulvans were analyzed by FT-IR and H1 RMN showing carboxyl and sulfate groups and they are constituted by rhamnose, rhamnose-3S, xylose and glucuronic acid, but not by iduronic acid. The antioxidant capacities of U. lactuca extracts were determined showing that ulvans are the main contributors to antioxidant capacity whereas ascorbate, glutathione, and phenolic compounds exert a minor contribution. To analyze whether ulvans and oligo-ulvans can stimulate plant growth, oligo-ulvans were prepared by acid hydrolysis and they were sprayed on A. thaliana leaves. Ulvans and oligo-ulvans increased A. thaliana biomass, fresh and dry weight, rosette diameter, number of leaves, and length of the main root, mainly oligo-ulvans. To determine whether the increase in plant growth may involve an enhanced basal metabolism and cell division, the level of transcripts encoding enzymes involved in C, N, and S assimilation, and proteins controlling cell cycle were analyzed. The expression of the latter genes was increased, mainly in response to oligo-ulvans. Thus, ulvans and oligo-ulvans stimulate growth of A. thaliana plants probably by increasing basal metabolism and cell division. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.